2021
DOI: 10.5296/jmr.v8i1.8494
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Capital Assets Pricing Model (CAPM) (Empirical Evidences from Amman Stock Exchange)

Abstract: The purpose of this study is to test the validity of CAPM in Amman Stock Exchange (ASE) during the period (2010 – 2014), which was divided into three sub periods. We used monthly returns of 60 stocks of Jordanian companies listed in ASE. Black, Jensen and Scholes (1972) and Fama and MacBeth (1973) methods were used to test the CAPM in different study sub-periods. The analysis results showed that higher risk (beta) is not associated with higher levels of return, which violated the CAPM assumption. Results of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Alqisie and Alqurran conducted a study to assess the accuracy of the Capital Asset Pricing Model (CAPM) in the Amman Stock Exchange from 2010 to 2014 [21]. Their findings demonstrated that an elevated level of risk (beta) did not correspond to an increased level of return, hence challenging the assumption of the CAPM.…”
Section: Relationship Between Esg Scores and Stock Betamentioning
confidence: 99%
“…Alqisie and Alqurran conducted a study to assess the accuracy of the Capital Asset Pricing Model (CAPM) in the Amman Stock Exchange from 2010 to 2014 [21]. Their findings demonstrated that an elevated level of risk (beta) did not correspond to an increased level of return, hence challenging the assumption of the CAPM.…”
Section: Relationship Between Esg Scores and Stock Betamentioning
confidence: 99%
“…The stock portfolio is divided according to the β coefficient of each stock. Alqisie, A., & Alqurran, T. [5] let the stock portfolio be divided by ordering the individual β coefficient of each stock in the sample, and each group contains the same number of stocks. In a similar way, we sorted the β coefficient of each stock from small to large, and divided the stock portfolio into a group of 4 stocks.…”
Section: Regression Analysis and Testmentioning
confidence: 99%
“…gde su: 𝑟̅ 𝑖 − 𝑟̅ 𝑓 -prosečna riziko premija na aktivu 𝑖, 𝛽 ̃𝑖procenjeni beta koeficijent aktive 𝑖. 1 Da bi CAPM model dokazao svoju apsolutnu ispravnost parametar 𝛾 0 ne bi trebalo statistički značajno da se razlikuje od nule, parametar 𝛾 1 bi trebalo da bude pozitivan i jednak tržišnoj ceni rizika 𝑟̅ 𝑚 − 𝑟̅ 𝑓 , koefici- 1 Procenjeni beta koeficijent se koristi umesto pravog beta koeficijenta, jer je pravi beta koeficijent nepoznat. jent beta bi trebalo da bude jedini faktor koji objašnjava stopu prinosa rizične aktive i mora postojati linearna zavisnost ostvarenog prinosa i sistemskog rizika merenog beta koeficijentom.…”
Section: Testiranje Validnosti Standardnog Capm Modelaunclassified